Comparative analysis reveals the long-term coevolutionary history of parvoviruses and vertebrates. - Matthew A Campbell; Shannon Loncar; Robert M Kotin; Robert J Gifford (PLoS Biology)
Parvoviruses (family Parvoviridae) are small DNA viruses that cause numerous diseases of medical, veterinary, and agricultural significance and have important applications in gene and anticancer therapy. DNA sequences derived from ancient parvoviruses are common in animal genomes and analysis of these endogenous parvoviral elements (EPVs) has demonstrated that the family, which includes twelve vertebrate-specific genera, arose in the distant evolutionary past. So far, however, such "paleovirological" analysis has only provided glimpses into the biology of ancient parvoviruses and their long-term evolutionary interactions with hosts. Here, we comprehensively map EPV diversity in 752 published vertebrate genomes, revealing defining aspects of ecology and evolution within individual parvovirus genera. We identify 364 distinct EPV sequences and show these represent approximately 200 unique germline incorporation events, involving at least five distinct parvovirus genera, which took place at points throughout the Cenozoic Era. We use the spatiotemporal and host range calibrations provided by these sequences to infer defining aspects of long-term evolution within individual parvovirus genera, including mammalian vicariance for genus Protoparvovirus, and interclass transmission for genus Dependoparvovirus. Moreover, our findings support a model of virus evolution in which the long-term cocirculation of multiple parvovirus genera in vertebrates reflects the adaptation of each viral genus to fill a distinct ecological niche. Our findings show that efforts to develop parvoviruses as therapeutic tools can be approached from a rational foundation based on comparative evolutionary analysis. To support this, we published our data in the form of an open, extensible, and cross-platform database designed to facilitate the wider utilisation of evolution-related domain knowledge in parvovirus research.